Traumatised between culture and religion: Women"s stories - Landman, Christina (HTS teologiese studies, 2012)
The majority of churches in South Africa offer some form of healing, be it diaconal, ritual or faith healing. Western and township views on healing differ significantly in terms of the natural and supernatural causes of and cures for illnesses. This article tells the stories of township women who were trapped between the binaries presented by Western, cultural and township healings, and their choicelessness in terms of abortion, adoption, abuse, death and sex. Through narrative counseling, based on social construction theories, the women experienced healing by exploring the healing spaces between the binaries of cultural contexts and Western medicine, through the liberty afforded them by the perspective of a preferred way of being.